2009
DOI: 10.1186/1471-2202-10-120
|View full text |Cite
|
Sign up to set email alerts
|

A secretory phospholipase A2-mediated neuroprotection and anti-apoptosis

Abstract: Background: Phospholipase A 2 liberates free fatty acids and lysophospholipids upon hydrolysis of phospholipids and these products are often associated with detrimental effects such as inflammation and cerebral ischemia. The neuroprotective effect of neutral phospholipase from snake venom has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…In a study using a neutral anticoagulant secretory phospholipase A 2 as a neuroprotectant, it has been shown that administration of secretory phospholipase A 2 reduced infarct volume in rats subjected to focal transient cerebral ischemia. Secretory phospholipase A 2 also alleviated the neuronal damage in organotypic hippocampal slices subjected to oxygen glucose deprivation (22). The authors also reported an increase in expression of AQP4 together with several anti-apoptotic and pro-survival genes.…”
Section: Up-regulation Of Aqp1 and Aqp4 Expression In Edema: A Survivalmentioning
confidence: 59%
See 1 more Smart Citation
“…In a study using a neutral anticoagulant secretory phospholipase A 2 as a neuroprotectant, it has been shown that administration of secretory phospholipase A 2 reduced infarct volume in rats subjected to focal transient cerebral ischemia. Secretory phospholipase A 2 also alleviated the neuronal damage in organotypic hippocampal slices subjected to oxygen glucose deprivation (22). The authors also reported an increase in expression of AQP4 together with several anti-apoptotic and pro-survival genes.…”
Section: Up-regulation Of Aqp1 and Aqp4 Expression In Edema: A Survivalmentioning
confidence: 59%
“…For infarct volume quantitation, whole rat brain slices were stained in 2,3,5-triphenyltetrazolium chloride (Sigma) and fixed in 10% buffered formalin. Stained brain slices were scanned, and the images were analyzed using Scion Image analysis software (22).…”
Section: Transient Focal Cerebral Ischemia and Quantitation Ofmentioning
confidence: 99%
“…ischemia and inflammation in various organs (21)(22)(23). Also, we do not know whether some of our patients had circulating tumor cells in Table II.…”
Section: Discussionmentioning
confidence: 97%
“…Animals were sacrificed at 0 hrs, 3 hrs, 6 hrs, 12 hrs, 24 hrs, 48 hrs, 72 hrs, 120 hrs and 168 hrs following MCAo and the brain samples were sectioned and subjected to infarct volume quantitation as described previously [10]. Infarct volume was measured by the indirect method formulation described by Swansson et al [11] and Lin et al [12].…”
Section: Methodsmentioning
confidence: 99%